046 EAST syndrome: probable closure in many an adult case. Issue 3 (9th February 2012) - Gandhi, D K; Philip, S; Agrawal, S; Wassmer, E; Gupta, R
Abstract : Introduction: It is frustrating for patients, families and clinicians when a unifying diagnosis for the constellations of neurological signs and symptoms remains elusive. Two recent reports, working independently, have hypothesised that KCNJ10 mutations on Chrosome 1q23.2 are responsible for Epilepsy, Ataxia, Sensorineural deafness and Tubulopathy (EAST syndrome/ SeSAME syndrome). We present a series of six patients with ages ranging from 3-22 years from three families. Case series: We describe three Asian siblings, two Caribbean siblings, and one Caucasian child who have epilepsy, ataxia, sensorineural hearing loss, and tubulopathy. Consanguinity was present only in the Asian family. Seizures were a presenting symptom in four with onset as early as 3–7 months of age. Development delay and learning difficulties were present in all of the cases. Ataxia was evident from early on. Sensorineural hearing loss was identified at different ages and in some cases was asymptomatic. In some cases, tubulopathy was an incidental finding. In the five children who have been extensively investigated, metabolic and mitochondrial investigations, magnetic resonance images, and electroencephalograms were normal. All six children had biochemical evidence of a tubulopathy with hypokalaemia, hypomagnesaemia, and alkalosis. KCNJ10 DNA mutations have since been identified in all of them. Conclusion: This condition does not seem to be life limiting as is evident from the early reports and our own experience. Three patients from our series have moved on to the adult services. We hypothesise that there are adult patients with similar findings who are still waiting for a closure.